2014
DOI: 10.1002/ajh.23645
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of a cohort of US patients with hemophilia B

Abstract: Hemophilia B (HB) is a disorder resulting from genetic mutations in the Factor 9 gene (F9). Genotyping of HB patients is important for genetic counseling and patient management. Here we report a study of mutations identified in a large sample of HB patients in the US. Patients were enrolled through an inhibitor surveillance study at 17 hemophilia treatment centers. A total of 87 unique mutations were identified from 225 of the 226 patients, including deletions, insertions, and point mutations. Point mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
(55 reference statements)
7
22
1
2
Order By: Relevance
“…It is also higher than the inhibitor incidence of 1.3% reported by Miller et al in a study of 153 American HB patients from 12 treatment centres [7], and the 2.1% inhibitor incidence found among 142 severe Canadian HB patients in the Canadian Haemophilia Registry [27]. However, in a cohort of 226 USA patients with HB, 17% of severe cases developed inhibitors [12]. This result is more similar to the results in this study.…”
Section: Stopsupporting
confidence: 86%
“…It is also higher than the inhibitor incidence of 1.3% reported by Miller et al in a study of 153 American HB patients from 12 treatment centres [7], and the 2.1% inhibitor incidence found among 142 severe Canadian HB patients in the Canadian Haemophilia Registry [27]. However, in a cohort of 226 USA patients with HB, 17% of severe cases developed inhibitors [12]. This result is more similar to the results in this study.…”
Section: Stopsupporting
confidence: 86%
“…ITI is haemophilia B is even more challenging than in haemophilia A. Inhibitors occur in 2–4% of patients with severe haemophilia B in most published series; 4·7% of 169 patients in an Italian series (Belvini et al , ), 2·1% among 142 in a Canadian series (Webert et al , ) and 1·3% among 153 in a series from the USA (Miller et al , ). A much higher frequency has been reported from Sweden, 19% of those with severe haemophilia B had developed inhibitors (Martensson et al , ) and a similar result, 17%, was also found in the series by Li et al (). The pathophysiology and risk factors of inhibitors in haemophilia B is much less known than in haemophilia A and patients may develop IgE antibodies that are usually detected at the same time and will provoke an allergic/anaphylactic reaction (Warrier et al , ; Chitlur et al , ; Goodeve, ).…”
Section: Iti In Haemophilia Bsupporting
confidence: 69%
“…Currently, 1094 unique variants of F9 gene have been identified in 3713 HB patients/pedigrees. The spectrum of F9 mutations varies among different population, and no data on the characteristics and spectrum of sporadic HB patients in China have been reported. In this study, we collected 294 unrelated HB families from different districts in China and identified 296 variants.…”
Section: Discussionmentioning
confidence: 99%
“…Most point mutations led to amino acid replacements, that is, missense mutations (68.3%, 164/240); and 46 point mutations (46/240, 19.2%) were nonsense mutations and caused premature termination…”
Section: Phenotype and Variant Spectrum Of Haemophilia Bmentioning
confidence: 99%
See 1 more Smart Citation